Bathymetric Measurements of the Vistula Smiala River Mouth with the Use of a Hydrographic Manned Vessel - Michal Skrzypek; Blażej Mach (Communications - Scientific letters of the University of Zilina, 2022)
The aim of the article was to present the characteristics of conducting bathymetric measurements of a water area by means of a manned watercraft. The survey was performed in a body of water that is relatively shallow and frequently used by water sports enthusiasts. The results of the study described the shape of the bottom of the marina studied and identified dangerous places for vehicles moving on it. It was proved that using a manned vessel is dangerous or impossible to make measurements near the pier where the yachts were moored and areas where the depth was less than 1 meter. Using the points recorded by the Lowrance HDS Carbon 9 echo sounder, the authors of this paper generated 2D and 3D maps of the measured reservoir with the depths plotted on them. The created studies can be used when developing navigational aids to facilitate the driving of water vehicles.